Increasing Cucumber Plant (Cucumis sativus L.) Growth and Production by Providing NPK Phonska and Gibberellin (GA3) - Alfrida Azizah; Rusmana; Imas Rohmawati; Alfu Laila (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Cucumber (Cucumis sativus L.) is a plant that has various advantages, one of which is a relatively short harvest period. This study was conducted to determine the most effective dose of NPK Phonska fertilizer and the optimal concentration of gibberellin growth regulator (GA3) to increase the growth and productivity of cucumber (Cucumis sativus L.) plants. This study was conducted from May to August 2025 at the Puri Serang Hijau, Serang City, Banten. The experiment was designed as a randomized block design with two treatment factors: the dose of NPK Phonska fertilizer (0, 350, 400, and 450 kg/ha) and the concentration of GA3 (0, 150, 175, and 200 ppm). The results showed that a single application of NPK Phonska fertilizer at a dose of 400 kg/ha gave the best effect on the growth and productivity of cucumber. This was reflected in greater plant height and more leaves, compared to other doses. The application of a single GA3 at a concentration of 200 ppm improved plant reproductive characteristics, such as accelerated flowering time. This study highlights the age of flower emergence and harvest age according to the varieties used as research objects.